Flipped classroom in neurophysiology: performance analysis of a system focusing on intrinsic students’ motivation - Ganfornina, Maria D.; Diez-Hermano, Sergio; Sanchez, Diego (Frontiers in Physiology, 2023)
Introduction: Teaching methodologies promoting active learning result in higher-order knowledge application, a desirable outcome in health disciplines like Physiology. Flipped-classroom (FC) promotes active learning and engagement in the classroom. Although specialized research keeps accumulating, the advantages of FC for improving academic outcome and ultimately patient care remain controversial and open to further analysis. Objective: This study evaluates the benefits of applying FC to the Neurophysiology module of a Human Physiology course. Methods:We compare final grades of students exposed to standard lecturing (five-years) vs. FC (six-years), and study the FC impact on student motivation, study time and rewards. Differing from conventional FC, we performed no pre-class/in-class assessments, relying on the students’ internal motivation to experience our FC model. A printed student workbook was designed as pre-class material for each session. Reading times respect the expected daily study time of students in our system. Results and discussion: Concerning academic performance, our long-term study reports a significant increase in average scores for FC groups. Overall, students get better scores in multiple choice tests than in problem-solving questions. A more detailed analysis uncovers that our FC model helps students to obtain better scores, reducing variability in performance due to assessment methods. Based on our open-ended survey questions, most students rate the FC environment and in-class activities positively and perceive a positive effect of FC on teachers’ performance. An objective automatic Sentiment analysis of open-ended answers reveals that FC is positively appreciated by students, associating positive perceptions to their understanding of physiological concepts, and negative evaluations to their time management.